Prevalence of sports injuries in group of Salamah Elderly School (Salsa) Larasati Bantul Yogyakarta - Arjuna, Fatkurahman; Suherman, Wawan Sundawan; Kristiyono, Kristiyono (Jurnal Pedagogi Olahraga dan Kesehatan, 2025)
This study aims to identify the prevalence of sports injuries in group of the Salimah Elderly School (SALSA) Larasati, Batul Regency, Yogyakarta. This study is a quantitative descriptive study with a retrospective approach based on questionnaire data filled out by the elderly. This study was conducted at the Secretariat of the Salimah Elderly School (SALSA) Larasati, Bantul Regency, Yogyakarta. The subjects in this study were 45 elderly people. The data analysis technique used descriptive analysis with a percentage. The results of this study obtained data that 27 respondents had never or had not experienced sports injuries, 6 respondents had dislocation or sprain injuries, 5 respondents had dizziness or blurred vision, 3 respondents had cracked or broken bones, 3 respondents had shortness of breath and 1 respondent had bruises. Of the respondents who experienced sports injuries, the treatment carried out on average was correct in accordance with the recommended treatment for sports injuries. Handling sports injuries in the elderly requires a special approach due to different physical conditions. It is important to focus on safe and effective recovery, as well as further prevention. The recommended treatment steps use the RICE method (rest, ice, compression and elevation) if a sports injury occurs in the elderly.